Efficacy of Integrated Nutrient Management in mango (Mangifera indica) cv. Kesar under semi-arid conditions of central Gujarat - KUMAR, RAJ; JADAV, J K; RAI, A K; KHAJURIA, S; LATA, K (The Indian Journal of Agricultural Sciences, 2017)
An experiment was carried out at KVK-Panchmahal, ICAR-CIAH, Godhra, Gujarat during 2014 and 2015 at five farmer’s orchards to find out the impact of RDF, biofertilizers and mulching on yield and qualitative attributes of mango (Mangifera indica L.) cv. Kesar in semi-arid conditions. Among the four treatments combinations, the maximum plant height (68%), stem girth (14.20%) and plant spread E-W (11.14%) and N-S (11.16%), yield (33.67kg/plant and 52.52 q/ha), TSS (16.290 brix), reducing (5.56 %), non-reducing (10.34 %) and total sugar (15.89%) was recorded when the plant treated with 75 % RDF + Azotobactor + PSB, each 250 g/plant) + mulching with grasses/straw @15 kg dry grass/sq m (T3) followed by RDF + mulching with grasses /straw @15 kg dry grass/sqm (T4), RDF (Recommended dose of manure (70 kg) and fertilizers @ N 1000g, P 750g and K 750 g /plant (T2) and control (T1). The maximum acidity (1.28 %) was recorded in T1 followed by T2 (1.19%) and T4 (0.75 %) and it was minimum in T3 (0.65%). The maximum cost of cultivation (Rupees 13 154/ha) was recorded in T2 and T4 followed by Rupees 12 686/ha in T3 and the same was minimum in T1 (Rupees 10 346/ha). The highest net returns (Rupees 41 831/ha) and cost benefit ratio (4.91) was computed in T3 followed by T4 (Rupees 39 831.40/ha and 3.33), T2 (Rupees 25 736.80/ha and 2.96) and T1 (Rupees 12 999.40/ha and 2.26). Results of the study revealed that the application of RDF (75%) + Azotobactor (250 g/plant) + PSB (250 g/plant)+mulching with grasses /straw (15 kg dry grass/sq m) were found to be more effective and can be applied to improve the vegetative growth, yield and quality of Kesar mango fruits. However, the application of RDF with grass mulching was also found to be better than bare RDF.